Pengukuran Parameter Fisika pada Sungai Idanoi Desa Sifalaete - Cindy Ardita Telaumbanua; Vebriman Jaya Halawa (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2025)
This research analyzes the physical parameters of the Idanoi River in Sifalaete Village, including color, odor, light penetration, depth, current speed, bottom substrate and vegetation. The results showed a brownish water color due to suspended particles, a muddy smell from organic sediment, and light penetration of 15 cm which indicated a high level of turbidity. The average current speed is 1.7157 seconds, with the wind influence being more dominant at the surface. The basic substrate is stone and gravel, while the vegetation around the river is dominated by grass and banana trees. Environmental factors and human activities influence river conditions, so monitoring and conservation are needed to maintain the ecosystem.